Effect of methionine on the radiobiological response of root meristem cells of Allium cepa L. seedlings - Герман, О. Ю.; Дика, Л. Д.; Еткало, К. М.; Гаркуша, Є. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The modification of radiobiological reaction by methionine has been studied in root meristem cells of onion seedlings of varieties Mavka and Veselka. The dose of gamma radiation of 40 Gy has a stimulating effect on mitotic activity and the dose of 200 Gy – depressing; both doses increase the level of cytogenetic damages. Methionine at a concentration of 1 mg/ml does not cause radioprotective effect, but on the contrary, significantly reduces the activity of cell divisions in both varieties in the control and under the action of radiation. In addition, methionine causes a significant increase of the level of cytogenetic damages. It has been suggested, that methionine methylating action causes the methylation of reparative proteins genes, which leads to the increase of cytogenetic damages level in variants with methionine. Although DNA methylation is a necessary process for passing of some phases of plant ontogenesis, in the period of seed germination, and in the conditions of stress excess of methyl groups inhibits normal development and adaptation of plants.